Minifilament Eruptions as the Last Straw to Break the Equilibrium of a Giant Solar Filament - Chen, Hechao; Tian, Hui; Zhang, Quanhao; Li, Chuan; Xia, Chun; Bai, Xianyong; Hou, Zhenyong; Ji, Kaifan; Deng, Yuanyong; Yang, Xiao; Hu, Ziyao (The Astrophysical journal, 2025)
Filament eruptions are magnetically driven violent explosions commonly observed on the Sun and late-type stars, sometimes leading to monster coronal mass ejections that directly affect the nearby planets’ environments. More than a century of research on solar filaments suggests that the slow evolution of photospheric magnetic fields plays a decisive role in initiating filament eruptions, but the underlying mechanism remains unclear. Using high-resolution observations from the Chinese H α Solar Explorer, the Solar Upper Transition Region Imager, and the Solar Dynamics Observatory, we present direct evidence that a giant solar filament eruption is triggered by a series of minifilament eruptions occurring beneath it. These minifilaments, which are homologous to the giant filament but on a smaller tempo-spatial scale, sequently form and erupt due to extremely weak mutual flux disappearance of opposite-polarity photospheric magnetic fields. Through multifold magnetic interactions, these erupting minifilaments act as the last straw to break the force balance of the overlying giant filament and initiate its ultimate eruption. The results unveil a possible novel pathway for small-scale magnetic activities near the stellar surface to initiate spectacular filament eruptions, and provide new insight into the magnetic coupling of filament eruptions across different tempo-spatial scales.